Design Improvements for Frequently Misrecognized Letters - Beier, Sofie; Larson, Kevin (Information Design Journal, 2010)
To enhance typeface legibility we studied how to improve the design of individual letters. Three different fonts were created, each containing several variations of the most frequently misrecognized letters. These variations were tested both with distance and short exposure methodologies. Creating variations within a typeface avoided confounds that occur when letters from different typefaces are compared against each other. The studies found that some variations were more legible than others despite the letters within a font having similar size, weight, and personality. The results showed that narrow letters benefit from being widened, and that x-height characters benefit from using more of the ascending and descending area.These findings can be used to improve the design of future typefaces.